Heart transplantation under coumarin therapy: friend or foe? - Karck, Matthias; Haverich, Axel (European journal of anaesthesiology, 1994)
Thirty-six patients were included in a retrospective study of the effect of pre-operative anticoagulant therapy on peri-operative blood loss and haemostatic changes after heart transplantation. Eleven patients (group H) had received intravenous heparin for at least 3 weeks before cardiac transplantation. Twelve patients (group P) had been transplanted when fully anticoagulated with phenprocoumon. A control group of 13 patients (group C) had undergone bypass grafting of their coronary arteries with no pre-operative anticoagulant therapy. Post-operative drainage from the chest drains was 700 ml (median) in group H, 425 ml in group P, and 360 ml in group C (group H vs. group C: P < 0.05). After heparinization for cardiopulmonary bypass, activated clotting time was 462 s (median) in group H, 1500 s in group P, and 727 s in group C (P < 0.003 vs. groups H and P). Post-operatively, patients in group P were given more units of fresh frozen plasma (median 2.5 units; P < 0.01), prothrombin complex concentrate (median 1000 I.U.; P < 0.05) and vitamin K (median 10 mg; P < 0.05) than groups H and C. Heart transplantation under full phenprocoumon therapy does not increase the likelihood of complications caused by peri-operative bleeding.
Gesehen am 12.01.2022